P2Y12 receptors in primary microglia activate nuclear factor of activated T‐cell signaling to induce C–C chemokine 3 expression. Issue 1 (24th February 2017) - Tozaki‐Saitoh, Hidetoshi; Miyata, Hiroyuki; Yamashita, Tomohiro; Matsushita, Katsuyuki; Tsuda, Makoto; Inoue, Kazuhide
Abstract: Microglia are widely accepted as surveillants in the central nervous system that are continually searching the local environment for signs of injury. Following an inflammatory situation, microglia alter their morphology, extend ramified processes, and undergo cell body hypertrophy. Extracellular nucleotides are recognized as a danger signal by microglia. ADP acting on P2Y12 receptors induce process extension of microglia thereby attracting microglia to the site of adenosine tri‐phosphate/ADP leaking or release. However, the question whether ADP/P2Y12 receptor signaling directly stimulates the production or release of inducible factors such as cytokines remains unclear. In this study, we found that CC chemokine ligand 3 (CCL3) is induced by ADP‐treated primary microglia. Pharmacological characterization using pertussis toxin, a P2Y12 receptor inhibitor, and a calcium chelator revealed that CCL3 induction was caused by P2Y12 receptor‐mediated intracellular calcium elevation. Next, nuclear factor of activated T‐cell dephosphorylation and nuclear translocalization were observed. Calcineurin, an inhibitor for nuclear factor of activated T cell, suppressed CCL3 induction. These data indicate that microglial P2Y12 receptors are utilized to trigger an acute inflammatory response in microglia via rapid CCL3 induction after ADP stimulation. Abstract : Extracellular nucleotides, like ADP, are recognized by P2Y12 receptors as a danger signal. Whether ADP/P2Y12 receptor signaling directly stimulates the production or release of inducible factors such as cytokines remains unclear. In this study, we demonstrate that ADP stimulates P2Y12 receptors, which leads to transient intracellular calcium increase and nuclear factor of activated T cell (NFAT) 1 activation. NFAT activation induces chemokine CCL3. These findings provide new concept that microglial P2Y12 receptors trigger an acute inflammatory response in microglia via NFAT activation leading to rapid chemokine induction, such as CCL3, after ADP stimulation.